Analisis Peran Pemerintah Desa Dalam Pemberdayaan UMKM Di Desa Sambirejo Kecamatan Binjai Kabupaten Langkat - Ika Bella; Sri Herlina; Rizky Fatmawati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to determine the role of village government in empowering MSMEs in Sambirejo Village, Binjai District, Langkat Regency. It also aims to identify the inhibiting and supporting factors in empowering MSMEs in Sambirejo Village, Binjai District, Langkat Regency. This research is a qualitative study, using interviews, observation, and documentation as data collection methods. The analysis used qualitative data analysis techniques, including written and oral data from several observed informants. In this case, the researcher attempted to provide a comprehensive overview of the village government's attention to MSMEs in Sambirejo Village. From the results of this study, it can be concluded that the role of the village government in empowering MSMEs in Sambirejo Village has been implemented but has not been optimal because the Sambirejo Village government programs have not fully helped MSMEs, this statement is also supported by the condition of MSMEs that have not been empowered, One of the obstacles that occurs to the government in efforts to empower MSMEs is the lack of budget and facilities owned by the Village government, which makes the village government less than optimal in empowering MSME actors in Sambirejo Village, Binjai District, Langkat Regency.